Treatment challenges in and outside a specialist network setting: Pancreatic neuroendocrine tumours. Issue 1 (January 2019) - ,; Hackl, Monika; Van Eycken, Elizabeth; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Pancreatic Neuroendocrine Neoplasms comprise a group of rare tumours with special biology, an often indolent behaviour and particular diagnostic and therapeutic requirements. The specialized biochemical tests and radiological investigations, the complexity of surgical options and the variety of medical treatments that require individual tailoring, mandate a multidisciplinary approach that can be optimally achieved through an organized network. The present study describes currents concepts in the management of these tumours as well as an insight into the challenges of delivering the pathway in and outside a Network.